Impact evaluation of seed replacement on pulse productivity in India - P, SHIVASWAMY G; KISHORE, AVINASH; JOSHI, KUHU; R, ANUJA A; SINGH, K N (The Indian Journal of Agricultural Sciences, 2022)
Pulses are traditionally an essential part of the Indian diet and primary protein source for the poorer and the vegetarian population in the country. Pulse productivity has been stagnant in India due to the widespread use of low-quality farm-saved seeds and low seed replacement rates. The present study was carried out during 2019–20 to assess the drivers of seed replacement and its ex-post impact on yields of chickpea and pigeonpea in India. The study is based on the data on 1764 chickpea and 944 pigeonpea farmers from the nationally representative Situation Assessment Survey of Agricultural Households conducted during 2013. A probit model was used to study the drivers of seed replacement, and coarsened exact matching technique used to assess the impact on yields causally. We found that access to irrigation and institutional credit can increase seed replacement and result in increased chickpea productivity. Chickpea farmers in districts under the National Food Security Mission on pulses (NFSM-pulses) are more likely to be replacing seeds. In pigeonpea, access to irrigation alone is the key driver. Further, using coarsened exact matching estimation, we found that seed replacement is indeed beneficial for chickpea farmers and would lead to increased chickpea productivity in India.